THE CONSTRUCTION OF THE INTEGRALIST VISION FROM THE CONTEMPORARY BIOLOGICAL-SOCIAL RELATIONSHIP – EXPERIENCE REPORT - Moraes Armesto, Leonardo; Roberto Alonso, Thabata (Journal of Interdisciplinary Debates, 2023)
The construction of a more airy and correct vision in the sense of understanding the influences and substantiations that the process of integration between knowledge as significant as corresponding, is the diametrical axis of the fundamental biological idea of being, as well as of a social prospect that formats the conduct , the formative perspectives and their most legitimate nuances. The experience report is based on the interpretation of impressions that connect the young-student-living being, to an association between anatomoformative flesh, to the foundations of the sociological meaning of life as an entity of meeting, reality and formative experience. The results showed rich and fertile discussions in the sense of giving vent to particular approaches and based on life experiences that keep undoubtedly valuable aspects of formation of each being involved.